STUDY OF THE STRAIN STATE AND MOVEMENTS OF A FLEXIBLE ROD WITH INITIAL CURVATURE - A. S. Lichkovakha; B. A. Shemshura; S. A. Kuznetsov (Вестник Дагестанского государственного технического университета: Технические науки)
Abstract. Aim. The possibility of obtaining the regressive part of the elastic (regressiveprogressive) characteristic under axial loading in the initial period is studied by applying an elastic rod having an initial curvature under vertical compressive load. The objective of the study is to determine the static characteristics of such a rod without taking the resistance forces into account. Method. To solve the problem, the elliptic parameters method was used to make a comparison with a solution obtained using the finite element method in the ANSYS engineering simulation software. Results. A technique was developed for assessing the strain state and displacements of a flexible rod with initial curvature in order to study the regression-progressive characteristic of various elastic systems having initial curvature for their effective use in determining oscillations. Conclusion. The obtained technique can be used to determine the deformed state of an elastic flexible rod having initial curvature and displacement of the point of application of force. At the same time, by setting various initial parameters of the flexible rod in order to obtain a regressive-progressive characteristic, significant displacements can be obtained in the subcritical region when the axial load does not exceed the Euler force for this flexible rod